ANTIHYPERURICEMIC EFFECT OF RED GINGER POWDER AND LIME JUICE COMBINATION IN WISTAR RATS INDUCED HYPERURICEMIA - Eva Susanty Purba; Chikita Dian Rahma Saphira; Salma Yasmine Azzahara; Edwin Basyar; Muflihatul Muniroh; Ainun Rahmasari Gumay (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background: Hyperuricemia is an abnormally high level of uric acid in the blood. Ginger and lime are natural ingredients that contain antioxidants and anti-inflammatory which could reduce blood uric acid levels. This study aims to prove the effect of red ginger powder and lime juice combination on uric acid levels of Wistar rats induced hyperuricemia.Methods: Experimental research with pre and post-test only control group design. Thirty Wistar male rats, aged 2-3 months, weighed 150-350 grams randomly divided into 5 groups. Group C1 was normal control group. Group C2 was induced by single intraperitoneal injection of potassium oxonate (300mg/kgBW). Group T1, T2, T3 were induced by potassium oxonate and orally administered by combination of red ginger powder (300, 600, 1200 mg/200gBW) and lime juice (2ml/150gBW). Blood samples in each group will be collected in 1 hour after treatment. Uric acid levels were measured using the TBHBA uric acid method.Results: Uric acid level in T1, T2, and T3 group was significantly lower than C2 group (p<0,05). The most effective dose to reduce uric acid levels was 1200mg/200gBW red ginger in combination with 2ml/150gBW lime juice (T3 group).Conclusion: Red ginger powder and lime juice may reduce the blood uric acid levels in Wistar rats induced hyperuricemia.